Effect of ascorbic acid supplementation on nitric oxide metabolites and systolic blood pressure in rats exposed to lead - Mohammad, Amani (Medknow Publications, 2010)
BACKGROUND: Extended exposure to low levels of lead causes high blood pressure in human and laboratory animals. The mechanism is not completely recognized, but it is relatively implicated with generation of free radicals, oxidant agents such as ROS, and decrease of available nitric oxide (NO). In this study, we have demonstrated the effect of ascorbic acid as an antioxidant on nitric oxide metabolites and systolic blood pressure in rats exposed to low levels of lead. MATERIALS AND METHODS: The adult male Wistar rats weighing 200-250 g were divided into four groups: control, lead acetate (receiving 100 ppm lead acetate in drinking water), lead acetate plus ascorbic acid (receiving 100 ppm lead acetate and 1 g/l ascorbic acid in drinking water), and ascorbic acid (receiving 1 g/l ascorbic acid in drinking water) groups. The animals were anesthetized with ketamin/xylazine (50 and 7 mg/kg, respectively, ip) and systolic blood pressure was then measured from the tail of the animals by a sphygmomanometer. Nitric oxide levels in serum were measured indirectly by evaluation of its stable metabolites (total nitrite and nitrate (NOχ)). RESULTS: After 8 and 12 weeks, systolic blood pressure in the lead acetate group was significantly elevated compared to the control group. Ascorbic acid supplementation could prevent the systolic blood pressure rise in the lead acetate plus ascorbic acid group and there was no significant difference relative to the control group. The serum NOχ levels in lead acetate group significantly decreased in relation to the control group, but this reduction was not significantly different between the lead acetate plus ascorbic acid group and the control group. CONCLUSION: Results of this study suggest that ascorbic acid as an antioxidant prevents the lead induced hypertension. This effect may be mediated by inhibition of NOχ oxidation and thereby increasing availability of NO.